2017
DOI: 10.5433/1679-0359.2017v38n3p1179
|View full text |Cite
|
Sign up to set email alerts
|

Hydration curve and physiological quality of maize seeds subjected to water deficit

Abstract: The hydration pattern associated with the physiological quality of seeds can be an early indicator for the evaluation of seed quality. The present study aimed to evaluate the hydration pattern of seeds subjected, or not, to water restriction, and to relate these patterns to their physiological quality. The physiological quality of seeds from five maize strains (L1, L2, L3, L4, and L5) and four hybrids (HT1, HT2, HS1, and HS2) was initially determined using seed germination and vigor tests (accelerated ageing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Similar trends have been reported by other researchers, who found a significant decline in the germination capacity of maize seeds as a function of reduced osmotic potential caused by polyethylene glycol 6000, helping to identify drought-resistant maize genotypes (Khayatnezhad, Gholamin, Jamaati-e-Somarin, & Zabihi-e-Mahmoodabad, 2010;Vaz-de-Melo et al, 2012;Abreu et al, 2014;Partheeban, Chandrasekhar, Jeyakumar, Ravikesavan, & Gnanam, 2017), as observed in the present study.In hydration with water, hybrid HT1 achieved protrusion in 36 hours and HT2 achieved protrusion in 48 hours; at -0.3 MPa, HT1 obtained protrusion in 48 hours and HT2 in 96 hours; and at -0.9 MPa, protrusion occurred in 72 and 168 hours for HT1 and HT2, respectively. According to Prazeres and Coelho (2017), root protrusion was achieved in less time in the high vigor hybrid (HT1) than its low vigor counterpart (HT2) for all of the osmotic potentials. Root protrusion was used as a reference point for the mobilization of the stored reserves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar trends have been reported by other researchers, who found a significant decline in the germination capacity of maize seeds as a function of reduced osmotic potential caused by polyethylene glycol 6000, helping to identify drought-resistant maize genotypes (Khayatnezhad, Gholamin, Jamaati-e-Somarin, & Zabihi-e-Mahmoodabad, 2010;Vaz-de-Melo et al, 2012;Abreu et al, 2014;Partheeban, Chandrasekhar, Jeyakumar, Ravikesavan, & Gnanam, 2017), as observed in the present study.In hydration with water, hybrid HT1 achieved protrusion in 36 hours and HT2 achieved protrusion in 48 hours; at -0.3 MPa, HT1 obtained protrusion in 48 hours and HT2 in 96 hours; and at -0.9 MPa, protrusion occurred in 72 and 168 hours for HT1 and HT2, respectively. According to Prazeres and Coelho (2017), root protrusion was achieved in less time in the high vigor hybrid (HT1) than its low vigor counterpart (HT2) for all of the osmotic potentials. Root protrusion was used as a reference point for the mobilization of the stored reserves.…”
Section: Resultsmentioning
confidence: 99%
“…Both hybrids were produced in the 2015/2016 growing season and provided by a local company in the municipality of Coxilha in the state of Rio Grande do Sul. Both were previously characterized in terms of vigor according to Prazeres and Coelho (2017). The HT1 hybrid showed higher germination (96%), higher vigor by accelerated aging (89%) and a low electrical conductivity (10.81 μS cm -1 g -1 ).…”
Section: Plant Materialsmentioning
confidence: 99%
“…This limitation of magnetic stimulation had already been reported; for this reason, there was no positive effect from the applied magnetic fields on the germination of onion seeds in studies carried out by Tkalec et al (2009). This may be because the use of electromagnetic fields in seeds alters the rate of water transport to the seed; it slows down germination, and it is directly dependent on hydration (Prazeres & Medeiros, 2017).…”
Section: Treatmentsmentioning
confidence: 88%